Phosphonic acid: preparation and applications - Sevrain, Charlotte M.; Berchel, Mathieu; Couthon, Hélène; Jaffrès, Paul-Alain (Beilstein Journal of Organic Chemistry, 2017)
The phosphonic acid functional group, which is characterized by a phosphorus atom bonded to three oxygen atoms (two hydroxy groups and one P=O double bond) and one carbon atom, is employed for many applications due to its structural analogy with the phosphate moiety or to its coordination or supramolecular properties. Phosphonic acids were used for their bioactive properties (drug, pro-drug), for bone targeting, for the design of supramolecular or hybrid materials, for the functionalization of surfaces, for analytical purposes, for medical imaging or as phosphoantigen. These applications are covering a large panel of research fields including chemistry, biology and physics thus making the synthesis of phosphonic acids a determinant question for numerous research projects. This review gives, first, an overview of the different fields of application of phosphonic acids that are illustrated with studies mainly selected over the last 20 years. Further, this review reports the different methods that can be used for the synthesis of phosphonic acids from dialkyl or diaryl phosphonate, from dichlorophosphine or dichlorophosphine oxide, from phosphonodiamide, or by oxidation of phosphinic acid. Direct methods that make use of phosphorous acid (H3PO3) and that produce a phosphonic acid functional group simultaneously to the formation of the P–C bond, are also surveyed. Among all these methods, the dealkylation of dialkyl phosphonates under either acidic conditions (HCl) or using the McKenna procedure (a two-step reaction that makes use of bromotrimethylsilane followed by methanolysis) constitute the best methods to prepare phosphonic acids.
Keywords: bromotrimethylsilane; hydrolysis; McKenna’s reaction; phosphonate; phosphonic acid